ANALISIS TRANSFORMASI DIGITALISASI MELALUI APLIKASI SISTEM INTEGRASI KONSTRUKSI TERHADAP PRODUKTIVITAS KERJA QUANTITY SURVEYOR PROYEK KONSTRUKSI BANGUNAN GEDUNG - Caesarani Gloria Putri; Sugeng Santoso (Universitas Mercu Buana, 2020)
In this study, the authors transformed the digitalization by using a construction integration system application in one of the building construction projects built by PT. X with the aim of compiling an analysis of system application digitalization transformation. Construction integration through re-engineering business processes to increase productivity so as to speed up the work time of surveyors and also to assess the impact of implementing the construction integration system on the quantity of surveyors. The results show that with the transformation of digitizing the use of the construction integration system application, procurement process becomes a more effective and efficient process in increasing productivity because it can reduce processes that are not needed in a procurement process. The impact of implementing this transformation is in the grouping of budgets / costs according to the scope of work and location, starting from making work orders and progressing the work, shortening the work progress transaction flow, and in controlling the work area that has been done. PT. X carried out the transformation by creating a construction integration system digitization program used in building construction projects. This transformation is implemented in all PT. X with the aim of increasing employee productivity in order to avoid project implementation time.